4-[(E)-1-Naphthyldiazenyl]phenol - Aslanov, Leonid A. (International Union of Crystallography, 2009)
The title compound (C. I. Solvent Yellow 8), C(16)H(12)N(2)O, crystallizes with two crystallographically independent molecules in the asymmetric unit. The planarity of both molecules is slightly distorted, the dihedral angles between the benzene ring and the naphthalene system being 9.04 (8) and 5.69 (3)°. In the crystal, O—H⋯N hydrogen bonds between the hydroxy groups and azo N atoms link the two symmetry-independent molecules into a polymeric chain propagating in [001].